2004
DOI: 10.1039/b307508g
|View full text |Cite
|
Sign up to set email alerts
|

Element selective characterization of stability and reactivity of selenium species in selenized yeast

Abstract: The concerted application of element specific atomic spectral detection for chromatographic eluent monitoring allows previously unexploited qualitative and quantitative analytical concepts to be developed for the determination of selenium species. Selenium speciation is vital in order to better understand its metabolism and biological significance in clinical chemistry, biology, toxicology, and nutrition. Fluoroacid ion pair HPLC with ICP-MS detection and GC derivatization with atomic emission detection (AED) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 36 publications
4
77
0
Order By: Relevance
“…1 shows the HPLC-ICP-MS chromatogram of the Life Extension Super Selenium Complex capsules. Comparisons with results for selenium supplements utilizing these HPLC conditions [40,51,52] confirm the peak identifications and show a complex selenium speciation including inorganic and organic compounds. The former (selenate and selenite) are quantifiable since the both elute after the void volume and no other anionic selenium species have ever been observed under these conditions.…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…1 shows the HPLC-ICP-MS chromatogram of the Life Extension Super Selenium Complex capsules. Comparisons with results for selenium supplements utilizing these HPLC conditions [40,51,52] confirm the peak identifications and show a complex selenium speciation including inorganic and organic compounds. The former (selenate and selenite) are quantifiable since the both elute after the void volume and no other anionic selenium species have ever been observed under these conditions.…”
Section: Resultssupporting
confidence: 56%
“…In 2004, we reported [51] the presence of a sulfur-selenium amino acid, S-(methylseleno)cysteine, in archived selenized yeast samples from the Clark study [42]. Its presence was subsequently confirmed by GC-AED [52] and 77 Se NMR [59].…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Analysis of archived samples of selenized yeast from the Clark trials showed that two additional Se compounds were sometimes present, in some cases in amounts together approaching or exceeding the level of 1. One of these unidentified compounds corresponds in retention time and mass spectral fragmentation to the hydrate of selenomethionine Se-oxide (2, MeSe(OH) 2 CH 2 CH 2 CH(NH 2 )CO 2 H) (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%